KESESUAIAN LAHAN TANAMAN KARET (Hevea brasiliensis) DI DESA GIRI NANTO KABUPATEN SELUMA - Chaula Lutfia S; Fauzul Azhimah (Universitas Quality, 2019)
Land resources are natural resources that are very important for human survival because natural resources are needed in every life. Land evaluation is an estimate of suitability for a particular land use in order to optimize the existing land in an area. This study aims to assess the suitability class of rubber plantations in environmental conservation efforts in Giri Nanto Village, Seluma Regency. The study was conducted in 2015 with a free survey method, analyzed descriptively qualitatively and quantitatively through an analysis approach to environmental impact and mapped through analysis using Arc.Gis software 10.0, land map units, and rubber land suitability criteria with a map scale of 1: 85,000. The results showed that the total area of potential land in the Giri Village area would later be 1,185 ha. The distribution of potential land suitability classes for rubber plants was mostly S2 land classes (quite suitable) covering 622.82 ha (8.9%), S3 class (marginal suit) covering 526.4 ha (7.5%), and land classes N (incompatible) covers 35.68 ha (0.5%) .The limiting factor for the potential S3 land suitability class (according to marginal) is 16-30% slope, and class N (not suitable), namely rough soil texture. Allowing closed land to slope> 40%, and the texture of coarse soil as a protected forest area are expected to function as an alternative to sustainable land conservation for environmental conservation.